2010
DOI: 10.1007/s10734-010-9400-0
|View full text |Cite
|
Sign up to set email alerts
|

What are the major impact factors on research performance of young doctorate holders in science in China: a USTC survey

Abstract: Doctoral graduate research performance (DRP) is recognized as one of the most critical indices for evaluation of the success of doctoral education. Doctoral graduates with high research performance directly reflect a higher ability in academic research and academic achievement. Consequently, identifying which factors influence DRP is potentially of great value. This topic is also challenging because of difficulties in identifying the impact factors on research performance and the feasibility of the relative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 53 publications
3
29
0
1
Order By: Relevance
“…This cohort appears to be particularly productive during doctoral candidature, confirming studies that suggest doctoral productivity is a predictor of future output (Williamson & Cable, 2003), and which interpret productivity during candidacy as an indicator of high research performance (Gu, Lin, Vogel, & Tian, 2011). Again, the role of the supervisor appears to be influential in encouraging and establishing research efficacy in this area, particularly through the practice of co-publication during candidature, with potentially several benefits for candidates.…”
Section: Discussionsupporting
confidence: 75%
“…This cohort appears to be particularly productive during doctoral candidature, confirming studies that suggest doctoral productivity is a predictor of future output (Williamson & Cable, 2003), and which interpret productivity during candidacy as an indicator of high research performance (Gu, Lin, Vogel, & Tian, 2011). Again, the role of the supervisor appears to be influential in encouraging and establishing research efficacy in this area, particularly through the practice of co-publication during candidature, with potentially several benefits for candidates.…”
Section: Discussionsupporting
confidence: 75%
“…With regard to the importance of cooperation (exchange), our interviews support fi ndings in the literature (Bland et al 2005 ;Gu et al 2011 ). Our results add further insights to the literature by revealing on which level exchange should be fostered: interviewees named most often that exchange should be fostered by the faculty rather than by other organizational levels.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the study by Bland et al ( 2005 ) indicated the importance of fostering external networks, which have been shown to be positively associated with high research performance. Likewise, in the study by Gu et al ( 2011 ), the importance of social networking was noted as an essential factor for Ph.D. students' research performance. According to this survey, the status of the academic origin of the Ph.D. student, the status of the advisor and the advisor's scientifi c experience and allocated energy (i.e., the time and energy spent) are strongly associated with Ph.D. students' research performance.…”
Section: Possibilities To Foster Work Motivation and Work Performancementioning
confidence: 84%
See 1 more Smart Citation
“…The Impact Factor has been used to reflect research performance and influence [51,52]. Our two groups had similar IF (Table 3), and were similar in terms of high quality journals (Q1 or Q2, Figure 3).…”
Section: Assessment Of Thesis-related Articles' Visibilitymentioning
confidence: 97%